Computer Network Security Third International Workshop on Mathematical Methods, Models, and Architectures for Computer Network Security, MMM-ACNS 2005, St. Petersburg, Russia, September 24-28, 2005, Proceedings - Gorodetsky, Vladimir; Kotenko, Igor; Skormin, Victor (Computer Communication Networks and Telecommunications, 2005)
This volume contains papers presented at the 3rd International Workshop on Mathematical Methods, Models and Architectures for Computer Network - curity (MMM-ACNS 2005) held in St. Petersburg, Russia, during September 25-27, 2005. The workshop was organized by the St. Petersburg Institute for Informatics and Automation of the Russian Academy of Sciences (SPIIRAS) in cooperation with Binghamton University (SUNY, USA). The 1st and the 2nd International Workshops on Mathematical Methods, Models and Architectures for Computer Network Security (MMM-ACNS 2001 and MMM-ACNS 2003), hosted by the St. Petersburg Institute for Informatics and Automation, demonstrated the keen interest of the international research community in the subject area. It was recognized that conducting a biannual series of such workshops in St. Petersburg stimulates fruitful exchanges between the di?erent schools of thought, facilitates the dissemination of new ideas and promotesthespiritofcooperationbetweenresearchersontheinternationalscale. MMM-ACNS 2005 provided an international forum for sharing original - search results and application experiences among specialists in fundamental and applied problems of computer network security. An important distinction of the workshop was its focus on mathematical aspects of information and computer network security addressing the ever-increasing demands for secure computing and highly dependable computer networks.